Diagnostic Value of Presepsin in Detection of Early-Onset Neonatal Sepsis - Ozdemir, Abdurrahman A.; Elgormus, Yusuf (American Journal of Perinatology, 2017)
Objective The aim of this study was to evaluate the efficacy of presepsin in both diagnosis and follow-up of early-onset neonatal sepsis (EOS) and also to compare its effectiveness with C-reactive protein (CRP) and procalcitonin (PCT).Methods A total of 29 term infants with EOS group and 40 term infants with control group were included in this study. Before initiating therapy, blood samples for whole blood count, CRP, PCT, presepsin, and culture were obtained from all neonates (T0). This procedure was repeated two times at 72 hours (T3) and day 7 (T7).Results Presepsin levels of sepsis group at T0 were significantly higher (704.27 ± 223.54 pg/mL) than the control group (508.33 ± 165.46 pg/mL). The sensitivity of CRP, PCT, and presepsin at T0 was found to be 83, 67, and 80%, whereas the specificity was found to be 75, 67, and 75%, respectively. The cutoff value for presepsin was 539 pg/mL with an area under the curve of 0.772.Conclusion Presepsin may be used as a reliable and accurate marker for both diagnosis and follow-up of EOS. However, to increase the accuracy, presepsin may be used in combination with other markers such as CRP and PCT.
Keywords: newborn; early-onset sepsis; presepsin; CRP; procalcitonin